MODEL PENGEMBANGAN MATERI PEMBELAJARAN SENI MUSIK DI SD/MI BERDASARKAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) - Udi Utomo (Jurnal Penelitian Pendidikan, 2010)
Although since 2006, Kurikulum Tingkat Satuan Pendidikan (KTSP) has been implied in elementary school/Islamic elementary school, but in its implementing there are still many teachers who find difficulties. From that reason, as the follow up of the previous research, this research will develop learning material model based on culture, creativity context, life skill, and enjoyable for students by noticing teachers‟ needs, environment and capability. The research locations determined purposively by establish three of special characterized towns in Central Java. This research uses Educational Research and Development which developed by Brogg and Gall (1983:775-76). Based on the previous research, the model of music learning material that developed in this research refers to three characteristics, they are (1) easy to be implemented by elementary school and Islamic elementary school teachers (applicable); (2) can be a comprehensive learning guidance, and (3) can be functionalized as learning media and source to teachers. The form is teaching materials that consist of: (1) learning materials belong to music knowledge and experience; (2) guidelines for teachers; and (3) supporting media (VCD). Development processes are done by four steps, they are (1) arranging learning material, teachers‟ guidance, and supporting media ( VCD); (2) expert review; (3) trial and (4) seminar. The trial model of music material development that developed in this research still done in limited target. From that reason, to know the feasibility for next betterment, it still needs continuation trial in broader target. So the model of music‟s learning material development is ready to be disseminated and implemented. Keywords: culture, creative, life skill and enjoyable.